Gap Structure of the Overdoped Iron-Pnictide Superconductor Ba(Fe0.942Ni0.058)2As2: A Low-Temperature Specific-Heat Study - Gang Mu; Bo Gao; Xiaoming Xie; Yoichi Tanabe; Jingtao Xu; Jiazhen Wu; Katsumi Tanigaki (Advances in Condensed Matter Physics)
Low-temperature specific heat (SH) is measured on the postannealed Ba(Fe1−xNix)2As2 single crystal with x = 0.058 under different magnetic fields. The sample locates on the overdoped sides and the critical transition temperature Tc is determined to be 14.8 K by both the magnetization and SH measurements. A simple and reliable analysis shows that, besides the phonon and normal electronic contributions, a clear T2 term emerges in the low temperature SH data. Our observation is similar to that observed in the Co-doped system in our previous work and is consistent with the theoretical prediction for a superconductor with line nodes in the energy gap.